(untitled) (Marketing Journal, 2025)
This article examines advanced approaches used for the rapid assessment of economic activity and elaborates the methodological and conceptual foundations for introducing the Business Activity Index (BFI) in Uzbekistan. Based on the analysis of internationa lly recognized indicators –such as the Purchasing Managersʼ Index (PMI), the IFO Index, and the Tankan Index –a tailored BFI methodology has been developed. The BFI enables the early identification of shifts in economic processes by utilizing prompt and near -real-time information in conditions where official statistics are formed with a time lag. In the study, sub -indices are constructed for key indicators, including production, new orders, employment, inventories, and price dynamics, after which an aggregate BFI score is calculated. The results demonstrate that the BFI serves as an effective analytical tool for assessing the current phase of the economic cycle, identifying regional differences in business activity, and generating short -term forecasts. The fin dings also justify the practical significance of applying the BFI for regular monitoring of the economic environment and supporting evidence -based policy decision -making in Uzbekistan.